2020
DOI: 10.21873/anticanres.14180
|View full text |Cite
|
Sign up to set email alerts
|

Positron Emission Tomography/Computed Tomography in Platinum-sensitive Recurrent Ovarian Cancer: A Single-center Italian Study

Abstract: Aim: To assess the correlation between contrastenhanced computed tomography (CE-CT) and positronemission tomography (PET)/CT results and surgical and pathological findings in patients with recurrent platinumsensitive ovarian cancer who underwent secondary cytoreduction. Patients and Methods: 18 F-fluorodeoxyglucose ( 18 F-FDG) PET/CT with/without CE-CT were performed before 56 cytoreductive surgeries in 49 patients with suspicious recurrent ovarian cancer. Results: 18 F-FDG PET/CT showed higher sensitivity and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 20 publications
0
18
0
1
Order By: Relevance
“…Another early report by Dirisamer et al indicated a higher sensitivity and specificity of PET/ceCT over PET/ldCT at the peritoneal level, in a small series of patients [27]. However, a recent series analysis by Gadducci et al could not confirm these results: both methods showed excellent sensitivity and accuracy at the patient level and performed relatively poorly in the detection of peritoneal deposits; the integration of ceCT to the PET examination brought no specific benefit [30]. In summary, although the PET/CT method and its combination with ceCT have been used for more than two decades, only a few studies performed a head-to-head comparison between the two diagnostic procedures.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Another early report by Dirisamer et al indicated a higher sensitivity and specificity of PET/ceCT over PET/ldCT at the peritoneal level, in a small series of patients [27]. However, a recent series analysis by Gadducci et al could not confirm these results: both methods showed excellent sensitivity and accuracy at the patient level and performed relatively poorly in the detection of peritoneal deposits; the integration of ceCT to the PET examination brought no specific benefit [30]. In summary, although the PET/CT method and its combination with ceCT have been used for more than two decades, only a few studies performed a head-to-head comparison between the two diagnostic procedures.…”
Section: Discussionmentioning
confidence: 95%
“…Some reports indicate that performing an 18 F-FDG PET with a full-dose CT and contrast medium might grant a better accuracy than 18 F-FDG PET with low-dose, non-contrast CT [27][28][29]. However, recent evidence was not able to confirm that using contrast medium and diagnostic settings significantly affect the accuracy of 18 F-FDG PET/CT [30]. In general, the use of "radiological" settings and contrast medium in CT has been debated for a long time; the consensus leans toward the possible usefulness of this technique in the context of abdominal lesions [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that PET-CT is especially useful for detecting recurrent ovarian cancer 18 19. In the period 2012–2016, when the patients in this study were recruited, only a few Norwegian hospitals had a PET scanner, which likely explains why this modality was used to detect recurrence in only 3% of patients.…”
Section: Discussionmentioning
confidence: 98%
“…e appearance of human changes with age. e surface of the young girl is smooth and uneven due to multiple ovulations after adolescence; the maximum postmenopausal volume of the ovary decreases during the sexual maturity [16]. Research shows that ovarian tumor is one of the common tumors of female genitalia [17], and its malignant tumor is the tumor with the highest mortality among gynecological malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, accuracy was used to represent the proportion of all predictions that were correct. e specific calculation method was shown in equation (15); Precision meant that all predictions were the ratio of positive examples where the actual labels were positive examples, and the specific calculation method was shown in equation (16). Recall was the ratio at which the positive sample was found, which could be calculated with equation (17).…”
Section: Evaluation Indicatorsmentioning
confidence: 99%